AB‐ Versus AA+BB‐Suzuki Polycondensation: A Palladium/Tris(tert‐butyl)phosphine Catalyst Can Outperform Conventional Catalysts. Issue 1 (1st December 2019) - Zhang, Kenan; Tkachov, Roman; Ditte, Kristina; Kiriy, Nataliya; Kiriy, Anton; Voit, Brigitte
Abstract: A Pd/P t‐ Bu3 catalyst having bulky, electron‐rich ligands significantly outperforms conventional "step‐growth catalysts" Pd(PPh3 )4 and Pd(P o ‐Tol3 )3 in the Suzuki polycondensation of the AB‐type arylene‐based monomers, such as some of the substituted fluorenes, carbazoles, and phenylenes. In the AA+BB polycondensation, Pd/P t‐ Bu3 also performs better under homogeneous reaction conditions, in combination with the organic base Et4 NOH. The superior performance of Pd/P t‐ Bu3 is discussed in terms of its higher reactivity in the oxidative addition step and inherent advantages of the intramolecular catalyst transfer, which is a key step joining catalytic cycles of the AB‐polycondensation. These findings are applied to the synthesis of a carbazole‐based copolymer designed for the use as a hole conductor in solution‐processed organic light‐emitting diodes. Abstract : The Pd/P t‐ Bu3 catalyst, having bulky, electron‐rich ligands, shows superior performance in the Suzuki polycondensation of AB‐monomers compared to conventional "step‐growth catalysts" Pd(PPh3 )4 and Pd(P o ‐Tol3 )3 . Furthermore, in combination with Et4 NOH, Pd/P t‐ Bu3 outperforms other catalysts in the polycondensation of AA+BB monomers. The obtained knowledge was successfully applied in the synthesis of practically important copolymers designed for solution‐processed organic light‐emitting diodes.